Ability of Non-Pathogenic Fusarium oxysporum Strain Fo47 to Suppress Rhizomania Disease of Sugar Beets in Morocco - Fatima NOUAYTI; Ilham MADANI; Abdessalem TAHIRI; Abdelali BLENZAR; Rachid LAHLALI (Notulae Scientia Biologicae, 2018)
Rhizomania is one of the most devastating diseases of sugar beet worldwide. The disease poses a serious threat to Moroccan production and it is capable of significantly decreasing quality and yield of sugar beet plantations. The long-term survival of its fungal vector (Polymyxa betae) in soil makes it a very difficult disease to manage. Therefore, this study investigated the potential of a non-pathogenic fungal Fusarium oxysporum strain Fo47 to control Polymyxa betae. This biocontrol agent was applied as soil treatment, seed treatment, or a combination of the both treatments. A bio-test was performed on treated soil. After four weeks of culture, the roots of sugar beet seedlings were retrieved and analyzed by the DAS-ELISA test. Results indicated that F. oxysporium Fo47 reduced the activity and survival of P. betae when compared to a reference biocontrol agent Trichoderma harzianum, which only revealed significant in reducing the viral load of Beet Necrotic Yellow Vein Virus (BNYVV) as seed treatment. The non-pathogenic Fusarium oxysporum Fo47 was more effective as soil treatment and allowed almost the same reduction of BNYVV virus concentration as T. harzianum 908. Therefore, our findings emphasizes that the performance of the biocontrol agent depends on the method of application.